Improving time efficiency gathering equipment in the treatment room. Issue 2 (26th October 2017) - Karapinar, Yesim; Habib, Ali; Sawyerr, Hannah
Abstract : Each junior doctor spends on average 29 hours a year just accessing treatment rooms and approximately 4 working days per year collecting equipment. We identified areas where time efficiency could be improved: accessing treatment room door codes, standardising access to equipment in treatment rooms throughout the hospital, implementing the 'procedure-specific' tray (one tray per procedure which includes all needed equipment in one place) and indexing equipment. Our aim was to reduce the time taken to collect equipment, promote best practice and aid timely medical intervention. We collected data from 24 junior doctors with a Likert scale questionnaire, which confirmed the problem. We then designed an experiment where we timed healthcare professionals accessing treatment rooms with no prior knowledge of the codes and then with codes provided securely on our hospital-issued iPad. We project a time saving of 703 hours (88 working days) at Northampton General Hospital (NGH) over 1 year. We then implemented our prototype 'procedure-specific trays' for common procedures (cannulation, lumbar puncture, catheter). We calculated how much time was saved when collecting equipment using our indexed 'procedure-specific' tray method compared with current practice. Based on our piloted trays, we project to save a total of 802 hours (100 working days) at NGH over 1 year. To finalise our project, we trialled our custom design trays based on our prototype for cannulation and demonstrated a time saving of 97% relative improvement: from 225 s to 7 s. According to these results, once full roll of 'procedure-specific tray' is achieved, the trust will save projected £30 100 per year (based on average junior doctor salary of £20 per hour).